2015
DOI: 10.2494/photopolymer.28.73
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive Polyimide for Packaging Applications

Abstract: Recently packaging technologies progress so much for high density, low profile and small foot print. For those applications, Photo sensitive polyimide (PSPI) applied as a re-distribution layer for the package. The PSPI was required to have good adhesion to wiring metal with low temperature curable nature. We developed the PSPIs with low temperature curability for emerging packaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Next, the sample was developed by cyclopentanone and rinsed by propylene glycol monomethyl ether acetate (PGMEA) at room temperature to form the lithography pattern. After the lithography process, the sample was cured at 280 °C for 1 hour by the oven (Yotec, DH-400N) under N2 atmosphere to complete the imidization of polyimide [14], [15].…”
Section: A Lithography Test Of Pspimentioning
confidence: 99%
“…Next, the sample was developed by cyclopentanone and rinsed by propylene glycol monomethyl ether acetate (PGMEA) at room temperature to form the lithography pattern. After the lithography process, the sample was cured at 280 °C for 1 hour by the oven (Yotec, DH-400N) under N2 atmosphere to complete the imidization of polyimide [14], [15].…”
Section: A Lithography Test Of Pspimentioning
confidence: 99%
“…Conventional positive-tone photosensitive polyimide is composed of alkali soluble polyimide precursor and napthoquinonediazide photosensitive compound (DNQ) [5]. In the conventional procedure for producing a polyimide, it was required to be heated up to 300 °C to complete imidization, leading to high shrinkage, outgassing, and high residual stress.…”
Section: Preparation and Pattern Formation Of Pspimentioning
confidence: 99%
“…Hence, photosensitive organic materials with low residual stress have been developed as interlayer dielectrics for semiconductor devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, Shoji et al had reported that a photosensitive preimidized polyimide (PI) with low residual stress is developed by introducing special soft segment and utilizing low temperature curable crosslinker [2].…”
Section: Introductionmentioning
confidence: 99%